TRAINING OF A TEACHER OF LABOR EDUCATION TO THE INTRODUCTION OF ENVIRONMENTAL EDUCATION IN THE EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2022)
In given article the concept of acolagical education and possibitiny ecological a nurman socien: as importat condition of formation ofecological education of schoolboys in the course of labour training is considered.
Keywords: ecologicał education